Análisis de desempeño del cableado estructurado del Gobierno Autónomo Descentralizado Provincial de Los Ríos - Barros Chang, Lorena Mariuxi (2019)
The performance of structured cabling implemented in the Gobierno Autónomo Descentralizado Provincial De Los Ríos (GAD Los Ríos) was evaluated, with the application of field tests using the cmd, iperf and jperf tools, an interview and an observation that allowed the networks and the level of data traffic that reaches the users of the institution. In contrast, the theory of livelihood and the data reached and determined: the scheduled maintenance wiring which affects its efficiency, poor hardware is used that produces anomalies and unsatisfactory performance. The performance of data transmission from the PS3-DT1 server to different points of the building small changes in latency and bandwidth with the client points in: mezzanine, ground floor, second and third floor